Blockchain-enabled cybersecurity framework for healthcare domain - Islam, Md Shohidul (2025)
Blockchain-enabled cybersecurity systems to ensure decentralised data transactions are gradually gaining popularity in the digital era for various areas like healthcare, education, finance, and transportation. The utilisation of blockchain in decentralised data transactions to enhance healthcare services has garnered increased attention within the healthcare sector, leading to improved facilities and services for a country. In recent years, health data transactions have usually been done in a traditional way, such as centralised data transactions where an intermediary or third-party server is used. Consequently, daily health data transactions carry the risk of privacy leaks and make data sharing and storage space capability difficulties. Although there are many existing studies for managing health data transactions with blockchain technology, there is inadequacy in the coordination of potential strategies of the existing frameworks. Additionally, different healthcare centers find it challenging to share information seamlessly and face significant cybersecurity issues because health data transactions often struggle with data integrity, confidentiality, and scalability. Addressing the aforementioned issues, this work focuses on decentralised data transactions in a blockchain-enabled healthcare ledger for the purpose of secure data storage and sharing. This research provides a full-fledged taxonomy by reviewing the relevant related works regarding the blockchain technology and the cybersecurity on distributed systems with heterogeneous networks. Accordingly, the main objective of this research is to propose a framework that provides secure health data transactions along with confidentiality, scalability, availability, and integrity in decentralised healthcare centers using blockchain. It also formulates the algorithms for the development of the proposed blockchain-enabled healthcare framework and evaluates its performance in data transaction management through simulation. This work delineates a blockchain-enabled healthcare framework and demonstrates the procedures for facilitating secure healthcare data transactions across different healthcare centers, allowing authorised healthcare providers to access the data. In the proposed system for health data confidentiality, blockchain provides a secure environment for the privacy-preserving health data management ledger through the hash SHA-256 technique and the consensus policy with transaction signature. The sequencing of each SHA256 hash checks and verifies any tampering of transaction data by hash, nonce, timestamp, and encoding value to ensure data integrity. This framework revealed the optimal performance in terms of mining health data size, average response time, transaction latency, and throughput for secured block transactions in blockchain networks by doing a simulation-based comparative study with the existing work. Scalability is indicated based on latency and balanced throughput across network nodes through the involvement of increasing health data sizes. Thus, this research expects the blockchain-enabled privacy-preserving data-retention design for health data transactions with integrity, confidentiality, scalability, and availability to enforce data access control policies in the healthcare domain.